Role of hypoxia inducible factor pathway in cardiorenal syndrome and application prospect of HIF stabilizer - A Rou-na; He Fang-fang; Sun Xin; Luo Chang-qing (Linchuang shenzangbing zazhi)
Cardiorenal syndrome （CRS） involves multiple organs. It refers to acute or chronic cardiac or renal dysfunction. Its pathophysiology involves immune inflammation，oxidative damage，anemia，iron metabolism disorders，dyslipidemia，hemodynamic disorders，endothelial dysfunction and neurohormonal mechanisms. Hypoxia is a common induced for the occurrence and development of cardiac or renal diseases. Up-regulated under hypoxia，hypoxia inducible factor （HIF） regulates the transcription of various target genes through multiple pathways and affects the pathogenesis of cardiorenal syndrome，such as inflammation，oxidative stress and lipid metabolism. Therefore HIF may become a potential therapeutic target for CRS. As a HIF stabilizer，HIF prolyl hydroxylase inhibitor can suppress the degradation of HIF so as to offer potential cardio-protective and renal-protective effects. Here the mechanism of HIF was reviewed for better understanding their links and exploring the application prospects of HIF stabilizerin CRS.